Asking more key questions of self-reflection. Issue 2 (4th March 2022) - Brownhill, Simon
ABSTRACT: The ability to reflect is fast becoming a skill that is globally recognised for its ability to benefit our learning, work and life. Support for individuals to engage in reflective activity can be found in an abundance of sources that include journal articles, online face-to-face coaching and mentoring opportunities, and published guides. However, when learners and professionals in the workforce seek to self-reflect, limited information is available at both a theoretical and practice-based level. Fuelled by concluding comments made in Asking key questions of self-reflection (Brownhill, 2022), this thoughtpiece offers a fresh literature-based exploration of this essential skill; this is facilitated by asking and answering more key questions such as who can and should self-reflect, and where and when can self-reflection be undertaken. Efforts to encourage individuals to engage in self-reflective activity are supported by a presentation of more stimulating ideas for use and adaptation. Written to be accessible in both content and scope, this thoughtpiece serves as an original and complementary 'go-to' that has the potential to help individuals self-reflect as part of their learning and/or professional development with increased clarity, appreciation and confidence.